Important Value Index (IVI) of Soil Macrofauna in the Traditional Oil Mining Area of Wonocolo - Tria Agustining Tyas; Laily Agustina Rahmawati; Solikhati Indah Purwaningrum (Advances in Tropical Biodiversity and Environmental Sciences, 2025)
The Wonocolo traditional oil mining area has oil exploitation activities that have the potential to affect the existence and diversity of soil macrofauna. Soil macrofauna play an essential role in maintaining the balance of the soil ecosystem through the processes of organic matter decomposition, nutrient cycling, and soil structure formation. This study aims to evaluate the Importance Value Index (IVI) of soil macrofauna in the Wonocolo traditional oil mining area and analyze the effect of mining activities on the macrofauna community. The research method employed is a quantitative descriptive approach, utilizing a stratified random sampling technique based on the density of oil wells per hectare. Data were collected through field observations, measurements of soil physical and chemical parameters (pH and temperature), and identification and quantification of soil macrofauna. Data analysis was conducted by calculating the IVI based on the density, frequency of presence, and dominance of each species. The results showed that traditional oil mining activities affected the composition and dominance of soil macrofauna. Several species had high IVI values, indicating their essential role in the soil ecosystem, while other species experienced population declines due to environmental changes. This study concludes that oil mining activities impact the existence and diversity of soil macrofauna; therefore, environmental management efforts are necessary to maintain the balance of the soil ecosystem in the area.